Detection of Mycobacterium tuberculosis from sputum samples of outdoor patients in Comilla, Bangladesh (Stamford Journal of Microbiology, 2020)
Tuberculosis (TB) caused by Mycobacterium tuberculosis has plagued humans since the beginning of history, but was on the decline after introduction of the Bacillus-Calmette-Guerin (BCG) vaccination programs. Tuberculosis appears to be an emerging problem worldwide due to environmental changes, mass migration and rise of drug-resistance phenomenon. This study targets to find out the distribution of TB patients in the sub-urban population around Comilla city in Bangladesh. A total of 455 patients with pulmonary symptoms were included in the study over a period of six months (from January 2016 to June 2016). Samples were smeared and stained with acid-fast technique and cultured in Lowenstein Jensen medium. A total of 2.4% of the patients were diagnosed with active pulmonary TB, 1.53% of whom are males and 0.87% are females. On the other hand, the Mantoux Tuberculin test showed 5.3% of these patients to be positive for TB, 3.3% of whom are males and 2% are females. 23% of the samples were sputum, 59% were pus, 14% were cerebrospinal fluid (CSF) and 4% were tracheal aspirates. On the whole, the suburban population around Comilla city in Bangladesh has a moderate incidence of pulmonary TB with military TB being rarely present. A thorough multi-year surveillance is needed to control the situation.Stamford Journal of Microbiology, Vol.9(1) 2019: 36-38